Empowering Postdoctoral Scholars: Insights From Library Focus Groups - Lena Bohman; Marla I Hertz; Regina Vitiello (Evidence Based Library and Information Practice)
Objective – The goal of this study was to assess how postdoctoral scholars (postdocs) engage with the campus library and identify barriers to access. Postdocs occupy a unique position within the research community, bridging the gap between graduate studies and permanent academic positions. Despite their critical role, there has been little formal research to examine how postdocs interact with library resources and services, likely due in part to their relatively small numbers at academic and research institutions.